Preoperative lignocaine nebulisation for attenuation of the pressor response of laryngoscopy and tracheal intubation in patients with severe preeclampsia undergoing caesarean section delivery: A randomised double-blind controlled trial - Fatma Nabil; Alaa Ahmed Gharib; Nawal Abdelaziz Gadelrab; Hany M Osman (Indian Journal of Anaesthesia, 2023)
Background and Aims: Following induction of general anaesthesia, direct laryngoscopy and endotracheal intubation usually cause tachycardia and hypertension due to increased sympathetic activity. This response is generally exaggerated in hypertensive patients. This study aimed to evaluate the effectiveness of preoperative lignocaine nebulisation in attenuating the pressor response to laryngoscopy and endotracheal intubation in patients with severe preeclampsia undergoing caesarean delivery. Methods: After ethical approval, we conducted this randomised, double-blind study, which included 110 patients with severe preeclampsia who underwent caesarean delivery under general anaesthesia. These patients were randomly allocated into two groups to receive either preoperative nebulisation of lignocaine 2% in a dose of 4.5 mg/kg (not exceeding 400 mg) in the lignocaine group or nebulisation of an equivalent volume of 0.9% NaCl in the saline group. The primary objective was the systolic blood pressure after tracheal intubation. The secondary objectives included heart rate, maternal serum cortisol and blood glucose levels, grade of cough during emergence, postoperative sore throat and hoarseness of voice, neonatal Apgar score and umbilical blood gas. Results: The systolic blood pressure was significantly lower in the lignocaine group compared to the saline group at 1, 3 and 5 min after endotracheal intubation and after delivery of the foetus (P = 0.001, 0.003, 0.002 and 0.019, respectively). Similarly, the heart rate was significantly lower in the lignocaine group versus saline group at 1 and 3 min after endotracheal intubation (P = 0.041 and 0.042, respectively). Conclusion: Preoperative lignocaine nebulisation in a dose of 4.5 mg/kg effectively attenuated the pressor response to laryngoscopy and endotracheal intubation in patients with severe preeclampsia undergoing caesarean delivery.